2003
DOI: 10.1097/00126334-200306010-00013
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Whole-Blood Finger-Stick Test for HIV Antibody: Performance and Acceptability Among Women in Northern Thailand

Abstract: Although use of rapid HIV antibody tests of finger-stick blood specimens could expand voluntary counseling and testing in areas where fear of venipuncture and delays in learning test results are barriers, there is little information on performance and acceptability of these tests in Asia. We used the Hema. Strip HIV-1/2 test (Saliva Diagnostic Systems, Vancouver, WA) in a prospective cohort study of HIV seroincidence among women in northern Thailand from 1998 to 1999. Nurses obtained whole-blood specimens by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The results also showed that clients prefer attending the services where they can get their results without delay [57, 5961]. This is consistent with the results of several studies reported that people who get tested preferred to receive their results on the test day [54, 59, 61]. …”
Section: Discussionsupporting
confidence: 84%
“…The results also showed that clients prefer attending the services where they can get their results without delay [57, 5961]. This is consistent with the results of several studies reported that people who get tested preferred to receive their results on the test day [54, 59, 61]. …”
Section: Discussionsupporting
confidence: 84%
“…A study from Cambodia demonstrated that 95.4% and 99.4% of women in antenatal clinics and labour, respectively, accepted rapid HIV testing 30. In a study from Chiang Rai Province, Thailand, 96.8% of women in antenatal and postnatal settings were satisfied with the rapid testing process and 78.7% of women said they preferred this process to conventional HIV testing 36. Several studies examined factors associated with acceptability of rapid testing, and found an increased uptake of testing in pregnant women who were over 21 years of age, with a higher educational status, earlier gestational age (<32 weeks), and who had less antenatal care during pregnancy 20…”
Section: Commentarymentioning
confidence: 99%
“…The number of false-positive determinations using HIV RTs has been surprisingly small even in low HIV prevalence populations where specificity would be expected to be reduced. International studies (USA, Peru, Thailand and India) have all shown HIV RTs specificities of 99.9% or greater in a population from antenatal clinics, sexually transmitted infection clinics and individuals having HIV occupational exposures [22][23][24][25][26][27]. The recent WHO report including ten HIV RTs tested on a wellcharacterized panel found specificities greater than 94.6% with four tests having 100% [28].…”
Section: Rapid Hiv Test Performancementioning
confidence: 99%
“…Although implementation and preferences for RTs and quick reporting are well documented at these venues [23,38,61,62], providing counselors to discuss both reactive and nonreactive results is still problematic in some places. Furthermore, there are reports that physicians sometimes would prefer a longer time before results were available so they have time to prepare to deliver the results to the patient.…”
Section: Barriers To Implementationmentioning
confidence: 99%